3D STRUCTURE AND FUNCTION ANALYSIS OF RECOMBINANT ALDII PROTEIN FROM Uncultured Acidilobus sp. USING I-TASSER - Meray, Nishia Waya; Suharti, Suharti; Akhmaloka, Akhmaloka (Jurnal Kimia Riset, 2024)
The AldII protein is a new recombinant protein produced from a novel gene obtained via a metagenome approach. Previous studies showed that this protein is strong and has the same metal binding aspect as the class II Aldolase enzyme. Aldolase is a valuable enzyme used in pharmaceuticals, food processing, and biochemistry. Further investigation is required to comprehend the structure and function of the AldII protein due to its potential. Researchers will conduct sophisticated bioinformatic analysis on the 3D shape and function prediction of AldII using the I-TASSER webserver from Zhanglab. The AldII protein is a new recombinant protein produced from a novel gene obtained via a metagenome approach. Previous studies showed that this protein is strong and has the same metal binding aspect as the class II Aldolase enzyme. Aldolase is a valuable enzyme used in pharmaceuticals, food processing, and biochemistry. Further investigation is required to comprehend the structure and function of the AldII protein due to its potential. Researchers will conduct sophisticated bioinformatic analysis on the 3D shape and function prediction of AldII using the I-TASSER webserver from Zhanglab. The I-TASSER server is an online tool for the automated prediction of protein structure and annotation of functions based on structure. Analysis of the AldII protein using the I-TASSER webserver shows that this protein has a stable structure with the closest structural homology to deoxyribose-phosphate aldolase from Bacillus thuringiensis with PDB code 6btdA. Additionally, the biological structure analysis shows that this protein shares the biological function of the enzyme L-fuculose-1-phosphate aldolase, which is part of the class II Aldolase enzyme that plays a role in the catabolism of arabinose, L-Fuculose, and Rhamnose. The results align with prior research that states the AldII protein is a stable protein with a catalytic side that is homologous to the class II Aldolase enzyme.